Pengembangan KOACI (Komik Aku Cinta Toleransi) Sebagai Media Dakwah Pembelajaran PAI Kelas 4 SD - Anisa Ayundasari; Meilina Azizah, Nurul; Zahra Nurmayusanti (STAI Terpadu Yogyakarta, 2024)
This research aims to develop e-comic learning media as a medium for preaching about the beauty of mutual respect in diversity for fourth grade elementary school students. This research uses the Design and Development (D&D) method with the ADDIE model which consists of five stages: analysis, design, development, implementation and evaluation. The population in this research is all fourth grade elementary school students. The sample in this study was 14 fourth grade students at SDN Sukamanah. The instruments used in this research were product validation questionnaires by material experts and media experts, as well as student response questionnaires. The results of this research show that the e-comic learning media developed is valid and suitable for use, and can increase students' understanding of the beauty of mutual respect in diversity, and students respond positively to e-comic learning media. So it can be concluded that the e-comic learning media “Komik Aku Cinta Toleransi” (KOACI) can be an effective alternative learning media to increase students' understanding of the beauty of mutual respect in diversity.